Effect of the atomic dipole relaxation and the pulse width on temporal cloaking. (8th March 2019) - Khan, R; Iqbal, M; Haneef, Muhammad; Bacha, B A; Khan, H; Bakhtawar,; Mariam,
Abstract: We investigated the effect of atomic dipole relaxation on temporal cloaking in a four-level N -type atomic system. Due to dipole relaxation rates, significant variation in the group index and in the advance/delay time of the probe pulse is noted. Temporal gaps of the order of nanoseconds are opened. Furthermore, multiple temporal gaps are created in a comparatively narrow probe pulse, whose quality is modified due to the width of the probe pulse and with the dipole relaxation rates. The results of this article will play a vital role in secure transmission and storage of information.